Recent Advances in the Applications of Triethylsilane in Organic Synthesis - Ručilová, Veronika; Soural, Miroslav (Synthesis, 2018)
The synthesis of pharmacologically relevant scaffolds is an important goal in modern organic chemistry. For this reason, the use of methodologies involving operationally simple procedures and easily handled reagents to chemoselectively and stereoselectively convert different functionalities has gained considerable attention. In this review, we summarize the latest trends in reductive reactions using triethylsilane as the key reagent that provide synthetically interesting intermediates, coupling products and structures with control of the 3D architecture.1 Introduction2 Scenario A: Reduction of C–C Multiple Bonds3 Scenario B: Reduction of Functional Groups4 Scenario C: Reductive Coupling5 Scenario D: Reductive Cyclization6 Conclusion
Keywords: triethylsilane; reduction; reductive coupling; reductive cyclization; heterocycles